Organic Peroxide-Sensing Repressor OhrR Regulates Organic Hydroperoxide Stress Resistance and Avermectin Production in Streptomyces avermitilis - Sun, Meng; Lyu, Mengya; Wen, Ying; Song, Yuan; Li, Jilun; Chen, Zhi (Frontiers in Microbiology, 2018)
The bacterium Streptomyces avermitilis is an industrial-scale producer of avermectins, which are important anthelmintic agents widely used in agriculture, veterinary medicine, and human medicine. During the avermectin fermentation process, S. avermitilis is exposed to organic peroxides generated by aerobic respiration. We investigated the role of MarR-family transcriptional regulator OhrR in oxidative stress response and avermectin production in S. avermitilis. The S. avermitilis genome encodes two organic hydroperoxide resistance proteins: OhrB1 and OhrB2. OhrB2 is the major resistance protein in organic peroxide stress responses. In the absence of organic peroxide, the reduced form of OhrR represses the expression of ohrB2 gene by binding to the OhrR box in the promoter region. In the presence of organic peroxide, the oxidized form of OhrR dissociates from the OhrR box and the expression of ohrB2 is increased by derepression. OhrR also acts as a repressor to regulate its own expression. An ohrR-deletion mutant (termed DohrR) displayed enhanced avermectin production. Our findings demonstrate that OhrR in S. avermitilis represses avermectin production by regulating the expression of pathway-specific regulatory gene aveR. OhrR also plays a regulatory role in glycolysis and the pentose phosphate (PP) pathway by negatively controlling the expression of pykA2 and ctaB/tkt2-tal2-zwf2-opcA2-pgl.